Development and validation of analytical HPLC method for quantification of curcumin in soybean oil nanocapsules - Ciocheta, Taiane Medeiro; da Silva, Taiz Martins; Viçozzi, Gabriel Pedroso; Reolon, Jéssica Brandão; Bender, Eduardo André; Colomé, Letícia Marques (Drug Analytical Research, 2026)
This study aimed to develop and validate an analytical methodology for quantifying curcumin in soybean oil nanocapsules. The chromatography separation used a C18 column (Phenomenex, 4.6 x 150mm, 5μm) and a ternary mixture of acetonitrile, acidified water (pH 3.0), and methanol (53:42:5). The flow rate used was 1 mL.min-1, and curcumin in the samples was detected at 425 nm. The chromatographic method proved specific for curcumin quantification and linear (correlation coefficient 0.9998). The limits of detection and quantification for the curcumin were 0.2575 µg.mL-1 and 0.7804 µg.mL-1, indicating the sensitivity of the analytical method. The repeatability and intermediate precision tests showed that the process is accurate (SRD less than 2%). In addition, the accuracy test showed values close to 100% for recovery of the bioactive. Thus, a new analytical method for quantifying curcumin in soybean oil nanocapsules may be used to analyze bioactive content.